2021
DOI: 10.3390/agriculture11080715
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sheep Behavior before Lambing

Abstract: The aim of this study was to assess the duration and frequency of behavioral observations of pregnant ewes as they approached lambing. An understanding of behavioral changes before birth may provide opportunities for enhanced visual monitoring at this critical stage in the animal’s life. Behavioral observations for 17 ewes in late pregnancy were recorded during two separate time periods, which were 4 to 6 weeks before lambing and before giving birth. It was normal farm procedure for the sheep to come indoors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Seminal plasma markers of fertility have been identified, while analytical molecular biochemistry investigates sperm genomics, proteomics, and epigenetics [ 1 , 2 , 3 , 4 ]. Biomedical sensors and technical equipment for the automated monitoring of the male animals have been involved in these prognostic efforts [ 5 ], and video cameras use is more and more involved in animal behavior studies. Waters et al [ 6 ] reported that visual observation of sheep lying and contractions could be utilized as an alert to the parturition progress.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal plasma markers of fertility have been identified, while analytical molecular biochemistry investigates sperm genomics, proteomics, and epigenetics [ 1 , 2 , 3 , 4 ]. Biomedical sensors and technical equipment for the automated monitoring of the male animals have been involved in these prognostic efforts [ 5 ], and video cameras use is more and more involved in animal behavior studies. Waters et al [ 6 ] reported that visual observation of sheep lying and contractions could be utilized as an alert to the parturition progress.…”
Section: Introductionmentioning
confidence: 99%